Where Are the Students in Efforts for Inclusive Excellence? Two Approaches to Positioning Students as Critical Partners for Inclusive Pedagogical Practices - Alison Cook-Sather; Anna DeVault; Nicole Litvitskiy; Tracie Marcella Addy (To Improve the Academy)
Most educational development for inclusive excellence does not draw directly on the experiences and perspectives of students. This article presents two different approaches to positioning undergraduate students as critical partners in developing inclusive pedagogical practices. Co-authored by the directors of and student partners who participated in each approach, the article defines inclusive excellence and inclusive teaching and provides selected examples of partnership work that strives for equity and inclusion. It then describes our different approaches, discusses potential benefits of launching student-faculty partnership work through these approaches, and offers recommendations for developing pedagogical partnership efforts for inclusive excellence at other institutions.